2018
DOI: 10.1103/physrevfluids.3.044601
|View full text |Cite
|
Sign up to set email alerts
|

Effect of texture randomization on the slip and interfacial robustness in turbulent flows over superhydrophobic surfaces

Abstract: Superhydrophobic surfaces demonstrate promising potential for skin friction reduction in naval and hydrodynamic applications. Recent developments of superhydrophobic surfaces aiming for scalable applications use random distribution of roughness, such as spray coating and etched process. However, most of previous analyses of the interaction between flows and superhydrophobic surfaces studied periodic geometries that are economically feasible only in lab-scale experiments. In order to assess the drag reduction e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 41 publications
1
18
0
Order By: Relevance
“…This approach, similar to that recently proposed by Zampogna, Magnaudet & Bottaro (2019) for rough walls, allows for a huge reduction of the computational cost of a direct numerical simulation (DNS) of channel flow: Seo & Mani (2016) have recently shown that a DNS using heterogeneous slip/no-slip boundary conditions would need a 12 times more refined computational grid compared to an equivalent computation using a homogeneous slip boundary condition. Recent DNS of turbulent flows over spatially heterogeneous boundary conditions, resolved up to the scale of the texture roughness (Seo & Mani 2016), have confirmed the trend found in experiments for both laminar (Choi et al 2003;Ou et al 2004) and turbulent regimes (Daniello et al 2009;Zhang et al 2015Zhang et al , 2016, as well as the theoretical predictions by Fukagata et al (2006), Seo & Mani (2018). Given the texture geometry, in most flow conditions the slip length L s is linearly dependent on the texture characteristic size L, up to a threshold value for which the high shear and pressure fluctuations will induce gas bubble depletion, resulting in a wetted (Wenzel 1936) state, providing an overall increase of the drag (Zhang et al 2016;Seo et al 2017;Gose et al 2018).…”
Section: State Of the Artsupporting
confidence: 68%
See 2 more Smart Citations
“…This approach, similar to that recently proposed by Zampogna, Magnaudet & Bottaro (2019) for rough walls, allows for a huge reduction of the computational cost of a direct numerical simulation (DNS) of channel flow: Seo & Mani (2016) have recently shown that a DNS using heterogeneous slip/no-slip boundary conditions would need a 12 times more refined computational grid compared to an equivalent computation using a homogeneous slip boundary condition. Recent DNS of turbulent flows over spatially heterogeneous boundary conditions, resolved up to the scale of the texture roughness (Seo & Mani 2016), have confirmed the trend found in experiments for both laminar (Choi et al 2003;Ou et al 2004) and turbulent regimes (Daniello et al 2009;Zhang et al 2015Zhang et al , 2016, as well as the theoretical predictions by Fukagata et al (2006), Seo & Mani (2018). Given the texture geometry, in most flow conditions the slip length L s is linearly dependent on the texture characteristic size L, up to a threshold value for which the high shear and pressure fluctuations will induce gas bubble depletion, resulting in a wetted (Wenzel 1936) state, providing an overall increase of the drag (Zhang et al 2016;Seo et al 2017;Gose et al 2018).…”
Section: State Of the Artsupporting
confidence: 68%
“…They also confirm that the solid fraction is the main parameter controlling both gas depletion and drag reduction: increasing this parameter ensures wetting-stable gas pockets, although providing a limited decrease of the friction. If on the one hand the presence of the plastron film produces a complex two-way interaction between the boundary and the external flow (Huang, Lv & Duan 2019), on the other hand, Seo & Mani (2018) have proven that the velocity and displacement of the gas-liquid interface is small enough to be neglected, provided that the surface texture is small enough not to trigger the onset of characteristic upwind travelling capillary waves. The flat air-liquid interface approximation used to model superhydrophobic surfaces sustaining laminar-turbulent transitional flows has been a posteriori justified by Seo & Mani (2018), who reported no appreciable flow modification in considering the free-surface dynamics while measuring drag reduction compatible with the ones measured by Gose et al (2018).…”
Section: State Of the Artmentioning
confidence: 99%
See 1 more Smart Citation
“…Next, we include more practical considerations to the presented analysis to make it more relevant to realistic applications. Our recent finding on the effect of texture randomness (Seo & Mani 2017) indicates that the maximum deformation angle of the randomly distributed textured SHS is about twice of the perfectly aligned posts considered in this study. For randomly distributed textured SHS, by spray coating or etched process, this geometric randomness will push the boundaries imposed by our analysis from aligned, periodic textured SHS as shown in figure 24(b).…”
Section: Boundary Map For Stable Shs Designmentioning
confidence: 47%
“…• Considering realistic surfaces that typically involve random posts, it is useful to extend the present DNS investigations to the case of surfaces with randomly distributed posts. In the limit of flat interface, Seo & Mani (2017) investigated the effects of randomness and quantified their impact on increased maximum stagnation pressure and deterioration of drag reduction performance. In the figures presented in Section 7, same trends were hypothesized for the capillary wave mechanism, but confirming this hypothesis requires a thorough and original investigation.…”
Section: J Seo R García-mayoral and A Manimentioning
confidence: 99%